2012
DOI: 10.1007/s10530-012-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in native micro-predator abundance explains recruitment of a mobile invasive fish, the common carp, in a naturally unstable environment

Abstract: Why certain species of fish become invasive is poorly understood and a key obstacle to restoring many of the world's ecosystems. In this study we tested whether variation in biotic resistance exerted by native predators might explain the reproductive success of the common carp, a large and fecund invasive species that typically spawns in outlying and unstable shallow habitat. An initial three-year study of the relative abundance of youngof-year (YOY) carp in interconnected lakes in the Upper Mississippi River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 44 publications
3
74
0
1
Order By: Relevance
“…Second, many adult carp have been found to aggressively move between interconnected lakes and into recently winterkilled wetlands and shallow lakes to spawn each spring when predator abundance is low (Bajer and Sorensen 2010). Third, detailed surveys of nearly two dozen lakes in the upper Mississippi River basin have found that high densities of young-of-the-year carp are only found in shallow interconnected lakes that have recently experienced winterkill and lack native fishes, Bluegills Lepomis macrochirus in particular (Bajer et al 2012). Fourth, when carp eggs have been placed into lakes with large numbers of native fishes, they have been found to disappear within a few days and seemingly before hatching (Bajer et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, many adult carp have been found to aggressively move between interconnected lakes and into recently winterkilled wetlands and shallow lakes to spawn each spring when predator abundance is low (Bajer and Sorensen 2010). Third, detailed surveys of nearly two dozen lakes in the upper Mississippi River basin have found that high densities of young-of-the-year carp are only found in shallow interconnected lakes that have recently experienced winterkill and lack native fishes, Bluegills Lepomis macrochirus in particular (Bajer et al 2012). Fourth, when carp eggs have been placed into lakes with large numbers of native fishes, they have been found to disappear within a few days and seemingly before hatching (Bajer et al 2012).…”
mentioning
confidence: 99%
“…Third, detailed surveys of nearly two dozen lakes in the upper Mississippi River basin have found that high densities of young-of-the-year carp are only found in shallow interconnected lakes that have recently experienced winterkill and lack native fishes, Bluegills Lepomis macrochirus in particular (Bajer et al 2012). Fourth, when carp eggs have been placed into lakes with large numbers of native fishes, they have been found to disappear within a few days and seemingly before hatching (Bajer et al 2012). However, while the latter results are compelling, they did not fully mimic natural scenarios as carp naturally spawn their sticky eggs onto extremely dense mats of floating vegetation in very shallow (<0.5-m) water where they presumably are not readily susceptible to predation (Swee and McCrimmon 1966;Crivelli 1980; P. W. Sorensen and P. G. Bajer, University of Minnesota, unpublished data).…”
mentioning
confidence: 99%
“…Nohner and Diana (2015) documented muskellunge egg transport (eggs found at the water's edge and onshore) in a study of northern Wisconsin, USA lakes, but did not quantify this observation. Predation can be an important source of egg mortality for scatter-spawning fishes (Fitzsimons et al, 2002;Caroffino et al, 2010;Bajer et al, 2012). Nilsson (2006) estimated that three-spined stickleback (Gasterosteus aculeatus) consumed 22.5% of northern pike (Esox lucius) eggs deposited in Kalmar Sound, Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it can have particularly strong effects on populations, greatly influencing recruitment of even the most fecund fish (Köster and Möllmann 2000;Bajer et al 2012). For example, in experimental ponds, egg predation by Orconectes virilis decreased or completely prevented recruitment of pumpkinseed (Lepomis gibbosus) and bluegill (L. macrochirus) sunfish respectively (Dorn and Mittelbach 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in experimental ponds, egg predation by Orconectes virilis decreased or completely prevented recruitment of pumpkinseed (Lepomis gibbosus) and bluegill (L. macrochirus) sunfish respectively (Dorn and Mittelbach 2004). Meanwhile, in the Upper Mississippi River Basin, egg predation by L. macrochirus drastically reduces carp recruitment, providing local biotic resistance to invasion by carp where the predator is present (Bajer et al 2012). Vulnerability to predation is conferred by the aggregated distribution and limited mobility of fish eggs and larvae (Hassell 1978;McGurk 1986).…”
Section: Introductionmentioning
confidence: 99%